STUDI KARAKTER MORFOLOGI KUCING PERANAKAN ANGGORA HASIL PERKAWINAN SILANG ALAMI - Nofisulastri Nofisulastri (Bioscientist : Jurnal Ilmiah Biologi, 2018)
This study aimed that to examine the extent of the diversity of morphological characters from random cross-breeding with mixtur  parental sources, then packaged to add material to the subject matter of Vertebrate Animal Systematics as a reference source for students of Biology Education Study Program FPMIPA IKIP Mataram. This research is a case study based on explorations descriptive that are presented qualitatively. A total of 24 cats were obtained by road sampling. Morphological characters include body color, color pattern, fur length, and tail length. The results showed that the frequency of appearance of morphological characters due to marriage in the same lineage led to the characteristics of mixtur race cats by 90.7% and 8.3% of domestic cats. Inline marriages (between siblings/mothers) tend to show large-medium round, high morphology, solid color patterns, thick fur, and long tails. While the appearance of short-tailed morphological characters leading to domestic cats and gray colors in low frequencies is thought to be the result of lethal and heterozygous genes derived.